Mutations in Twinkle primase-helicase cause Perrault syndrome with neurologic features - Morino, Hiroyuki (Neurology, 2014)
OBJECTIVE: To identify the genetic cause in 2 families of progressive ataxia, axonal neuropathy, hyporeflexia, and abnormal eye movements, accompanied by progressive hearing loss and ovarian dysgenesis, with a clinical diagnosis of Perrault syndrome. METHODS: Whole-exome sequencing was performed to identify causative mutations in the 2 affected sisters in each family. Family 1 is of Japanese ancestry, and family 2 is of European ancestry. RESULTS: In family 1, affected individuals were compound heterozygous for chromosome 10 open reading frame 2 (C10orf2) p.Arg391His and p.Asn585Ser. In family 2, affected individuals were compound heterozygous for C10orf2 p.Trp441Gly and p.Val507Ile. C10orf2 encodes Twinkle, a primase-helicase essential for replication of mitochondrial DNA. Conservation and structural modeling support the causality of the mutations. Twinkle is known also to harbor multiple mutations, nearly all missenses, leading to dominant progressive external ophthalmoplegia type 3 and to recessive mitochondrial DNA depletion syndrome 7, also known as infantile-onset spinocerebellar ataxia. CONCLUSIONS: Our study identifies Twinkle mutations as a cause of Perrault syndrome accompanied by neurologic features and expands the phenotypic spectrum of recessive disease caused by mutations in Twinkle. The phenotypic heterogeneity of conditions caused by Twinkle mutations and the genetic heterogeneity of Perrault syndrome call for genomic definition of these disorders.